Design a CVT lubricant test device - Azlan, Mohd Azwir (2006)
The technology of metal pushing V-belt (MPVB) Continuously Variable Transmission (CVT) is n o w commercially available in the market but to date the questionable reliabilities and limited torque capabilities have inhibited their growth. Belt slip is one of the major losses that cause inefficiency in CVT and limited the t r a n s f e r r e d torque f r om the engine to the tyres. One of the factors that believe cause this belt slip is because of unstable in oil lubricant behaviour especially due to operate in high temperature and pressure. Therefore, this report presents the work which has been carried out on designing a C V T Lubricant Test Device which capable to investigate the phenomena of f i lm collapse in a C V T mechanism. Modern design concepts and methods have been applied in designing this device where a five phase design model as proposed by Eggert has been used. The five phase designs are formulation, conceptual design, configuration design, parametric design and detail design. The device is significant because, hence to study and investigate film collapse, this device also capable to study and investigate the other specific parameters which affect the transmission efficiency such as differ in contact angle, contact area and material used.